2022
DOI: 10.1007/s00259-021-05672-x
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical and exploratory human studies of novel 68Ga-labeled D-peptide antagonist for PET imaging of TIGIT expression in cancers

Abstract: Purpose While TIGIT has been propelled as a next-generation target in cancer immunotherapy, anti-TIGIT therapy seems to be promising for a fraction of patients in clinical trials. Therefore, patient stratification is critical for this therapy, which could benefit from a whole-body, non-invasive, and quantitative evaluation of TIGIT expression in cancers. In this study, a 68 Ga-labeled D-peptide antagonist, 68 Ga-GP12, was developed and validate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…30 A gallium-68 labeled peptide targeting TIGIT ([ 68 Ga]Ga-GP12) has been evaluated for PET imaging of TIGIT. 31 PET imaging in a tumor-bearing mouse model revealed optimal tumorto-muscle ratio 60 min after tracer injection. Pretreatment with excess GP12 reduced the PET signal, whereas pretreatment with an anti-TIGIT monoclonal antibody did not, indicating binding to another epitope.…”
Section: Other Immune Checkpointsmentioning
confidence: 94%
“…30 A gallium-68 labeled peptide targeting TIGIT ([ 68 Ga]Ga-GP12) has been evaluated for PET imaging of TIGIT. 31 PET imaging in a tumor-bearing mouse model revealed optimal tumorto-muscle ratio 60 min after tracer injection. Pretreatment with excess GP12 reduced the PET signal, whereas pretreatment with an anti-TIGIT monoclonal antibody did not, indicating binding to another epitope.…”
Section: Other Immune Checkpointsmentioning
confidence: 94%
“…Shaffer et al (2021) have developed 64 Cu-TIGITmAb and 89 Zr-TIGITmAb to visualize TIGIT expression in murine models [41]. Additionally, Wang et al ( 2022) have used 68 Ga-GP12 to visualize TIGIT expression and evaluate safety in mouse models and two NSCLC patients [42]. Both studies showed higher tracer uptake in tumor lesions as compared to healthy organs.…”
Section: Tracer Features/validation Statementioning
confidence: 99%
“…In recent years, the commercial availability of more suitable chelators, such as NOTA and (Tris(hydroxypyridinone) (THP), allow 68 Ga labelling to be performed under milder conditions (37–60 °C). Typically, 68 Ga labelling for immune response are almost exclusively paired with these two chelators [ 113 , 117 , 118 , 119 ].…”
Section: Pet Imaging Of Immune Checkpointsmentioning
confidence: 99%
“…Another inhibitory immune checkpoint molecule, TIGIT, is also an interesting target for PET imaging. Additionally, [ 68 Ga]Ga-NOTA-GP12, a peptide antagonist for TIGIT, was demonstrated to be safe and able to image TIGIT expression in murine models and two patients with advanced NSCLC [ 117 ]. Nevertheless, further clinical evaluation is necessary to determine its potential value in predicting and monitoring response to ICIs.…”
Section: Pet Imaging Of Immune Checkpointsmentioning
confidence: 99%